Education for Disaster Risk Perception as a Priority of the Educational Work in the Schools of Cuba - Jiménez-Denis, Osmel (2017)
The Caribbean region and, particularly, the Cuban archipelago are systematically affected by multiple natural phenomena, which cause significant material damages and the loss of human lives. That is why the National Strategy on Environmental Education in Cuba declares as prioritized aspect population preparedness against hazards, vulnerability, and risks. In this regard, this review article discusses the theoretical and methodological foundations that underpin the education for disaster risk perception in the context of the educational processes in the schools of Cuba from the perspective of environmental education for sustainable development.